2011
DOI: 10.1177/0044118x11417979
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Want to Live Like This Anymore”

Abstract: This article reports on interview data gathered from 27 young people involved with a street-level service for young people considered "at risk" of diagnosis of personality disorder. Interviews with a self-selecting sample of young people explored the events that led to their initial contact with the service. Using Silverman's twin-track approach, narrative analysis provided a description of "how" these young people describe their lives in terms of "I don't want to live like this anymore" while "what" they desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A qualitative study examining BPD patients’ life stories revealed themes of low self-worth and struggling with gaining control over emotions, behavior, and purpose in life ( 36 ). Furthermore, Gilbert et al ( 37 ) examined life story interviews with people who had manifested features of PD. Findings showed that many expressed a sense of powerlessness and inability to initiate change, indicating an association between PD and low agency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study examining BPD patients’ life stories revealed themes of low self-worth and struggling with gaining control over emotions, behavior, and purpose in life ( 36 ). Furthermore, Gilbert et al ( 37 ) examined life story interviews with people who had manifested features of PD. Findings showed that many expressed a sense of powerlessness and inability to initiate change, indicating an association between PD and low agency.…”
Section: Introductionmentioning
confidence: 99%
“…During life story interviews, patients reported experiencing complex family dynamics, neglect, and feelings of being different or distant from others. Many individuals also reported struggling with developing trusting relationships ( 1 , 37 , 38 ).…”
Section: Introductionmentioning
confidence: 99%